PERANCANGAN SISTEM TATA UDARA PADA RUANG NICU DI LANTAI 3 RUMAH SAKIT “X” - Annisa Pramudhita (P3M Politeknik Negeri Indramayu, 2020)
In order to reduce nosocomial infections, or generally known as Hospital-acquired Infections (HAIs) in NICU room, a special design of air conditioning system is needed, as per HVAC Design Manual for Hospital and Clinics. There are several parameters that concerned in air conditioning design such as temperature, Relative Humidity (RH), room pressure, air cleanliness, ventilation and room air distribution. Cooling Load Temperature Difference (CLTD) will be the main method in this research. Meanwhile, Equal Friction Loss method will be used in air duct sizing. From calculation, obtained that cooling load capacity 8,805 kW. Meanwhile heating capacity obtained 3,660 kW. Total pressure loss value for design air duct is 44,85 Pa.. Pre-filter and medium filter was built-in at AC unit, so HEPA filter is needed to be mounted in ceiling.